An exploratory study on perception of adolescent girls towards early menarche in a union territory of India - Periyasamy, Saranya; Kittu, Devi; Debasish, Lopamudra (International Journal Of Community Medicine And Public Health, 2024)
Background: Early menarche is always a challenging one for adolescent girls since it is often associated with inadequate knowledge regarding puberty, adverse reproductive health outcomes and mental health problems. The objective of this study was to explore the perception and attitude of adolescent girls towards early menarche. Methods: A qualitative study was conducted in the rural field practice area of a Medical College in Puducherry during January to March 2022. The study participants (adolescent girls) were selected by means of purposive sampling. Four Focus Group Discussions were conducted among adolescent girls using an interview guide. The contents were transcribed and codes were derived. The codes were combined to form categories and finally, themes were generated and were interpreted. Results: Menarche was a shocking experience for the adolescent girls and there was no mental preparedness for accepting it and attaining menarche even earlier, made it still worse. They felt that they lost their childhood identity at a younger age as they looked more matured compared to their peers. They were unable to adjust themselves and it affected their psychosocial state. According to them, factors such as obesity, improper dietary habits, physical inactivity, and also mothers with early age of menarche were the causes of early menarche. Conclusions: The study participants felt that they had an inadequate knowledge about early menarche and they also found it difficult to cope up with ‘sudden changes into womanhood’. Assuming gender specific roles in their families made them stressed and feels helpless.